STUDENTS RESPONSES TOWARD IMPLEMENTATION OF C-MAP TOOLS IN PHYSICS LEARNING - NUR CAHYANI, DIDIN; SUPRAPTO, NADI (Inovasi Pendidikan Fisika, 2019)
This research aims to describe students? response toward the implementation of C-Map Tools in Physics Learning. This research used quantitative research method. The participant of this study was 36 students of natural science group Senior High School One of Menganti. The instrument research was student responses questionnaire. The questionnaire consists of 12 statements in term of response in motivation, independently, novelty and mastery of concept. Based on data analysis, student responses questionnaire, it can be concluded that student response toward the implementation of C-Map Tools to Physics Learning got a percentage 72,97 % with a good category. Keywords: C-Map Tools, Students Response and Physics Learning.